1988
DOI: 10.1177/089198878800100103
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Diabetic Neuropathy: A Complex Relationship

Abstract: In a group of 64 non-insulin-dependent diabetic females, a significant positive correlation between Zung self-rated depression scores and objective measurements of diabetic peripheral neuropathy was limited to those women with Zung scores greater than 50 (depressed group, n = 12). In the overall group, there was no significant linear or quadratic relationship between peripheral neuropathy and depression scores. The associations between depression, peripheral neuropathy, and diabetes are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…The results of the MANOVA indicated there were significant differences among For the majority of symptom severities (items [1][2][3][4][5][6][7][8][9][10][11][13][14][15][16][17][18][19], the pattern was similar to the symptom prevalence observations. Patients with depression reported more severe symptoms than the group with diabetes only, and depressed patients with and without diabetes reported similar levels of symptom severity ( Figure 3).…”
Section: -15 16-23 Total Bdi Scoresupporting
confidence: 68%
See 1 more Smart Citation
“…The results of the MANOVA indicated there were significant differences among For the majority of symptom severities (items [1][2][3][4][5][6][7][8][9][10][11][13][14][15][16][17][18][19], the pattern was similar to the symptom prevalence observations. Patients with depression reported more severe symptoms than the group with diabetes only, and depressed patients with and without diabetes reported similar levels of symptom severity ( Figure 3).…”
Section: -15 16-23 Total Bdi Scoresupporting
confidence: 68%
“…There is evidence that depression in diabetes can be diagnosed with reasonable sensitivity despite the potential under-diagnosis of depression (and other psychiatric conditions) associated with this diagnostic rule (1). This finding provides some methodologic support to observations that major depression is significantly more common in patients with diabetes than in the general US population (2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
Section: Introductionsupporting
confidence: 54%
“…In this study, neuropathy and negative attitude toward feet predicted development of a first ulcer. These data may reflect the complex relationship between depression and neuropathy [18,20].…”
Section: Consequences Of Foot Complications In Diabetic Patientsmentioning
confidence: 92%
“…This study of 14 patients and 11 caregivers reported that reduction in social activities, increased family tensions, lost time from work, and negative effects on general health were experienced by both groups. The enormous impact of lack of mobility in everyday living for both the patient with ulceration and for his or her caregivers led Brod [20] to refer to the condition as "the burden of a non-weight-bearing" regimen. This may explain some of the reasons for the counterintuitive findings that ulceration may affect quality of life more than amputation does: those fitted with prostheses are encouraged to be mobile, whereas those with an ulcer are not.…”
Section: Consequences Of Foot Complications In Diabetic Patientsmentioning
confidence: 98%
“…Evidence from individual studies [7][8][9][10], supported by a meta-analysis [11], suggests that there is a link between DPN and depressive symptoms. However, previous studies have focused almost exclusively on severe neuropathic pain, even though less than a third of patients with DPN experience painful symptoms [12] and many experience no symptoms [13].…”
Section: Introductionmentioning
confidence: 99%